Climbing the economic ladder : the role of outward foreign direct investment - Lim, Guanie (2018)
This paper argues that, under certain conditions, outward foreign direct investment (FDI) can promote economic development in the home economies from which the investment originates. It presents a conceptual framework incorporating simultaneously the complex interrelationships between the three main tenets shaping the developmental outcomes of outward FDI – the home economy conditions that induce firms to invest abroad; the role of the state in linking outward investment to economic development back in the home economy; and the investment returns which stimulate catching-up. The framework helps researchers and policymakers assess particular characteristics of outward FDI and their impacts on the home economies.